Physiology of nostril breathing exercises and its probable relation with nostril and cerebral dominance: A theoretical research on literature - Upadhyay-Dhungel, K; Sohal, A (Janaki Medical College Journal of Medical Science, 2013)
This article discuss about scientific basis of benefits of practicing slow pranayama, especially alternate nostril breathing pranayama. It explains the basis of benefit of alternate nostril breathing exercises and its probable relation with nasal cycle, cerebral dominance and autonomic nervous system. The airflow through one nostril is greater than next at any point of time which later switches to another. This is called nasal cycle. The nasal cycle lasts from 30 minutes to 2-3 hours. The nasal cycle occurs naturally. This nasal cycle is related with the cerebral dominance. When one nostril is dominant, the contra lateral hemisphere is active. The right nostril breathing leads to increased sympathetic activity while left nostril breathing decreases sympathetic activity and increases parasympathetic tone. So it has been speculated that these three phenomenon viz. nasal cycle, cerebral dominance and autonomic activities are correlated. This review also suggests that practicing alternate nostril breathing (Nadisodhan pranayma) regularly keeps the two hemispheres active and balances the sympathetic and parasympathetic activities in the body. Sympathetic or parasympathetic activity alternates automatically in our body which is important for our survival. Due to our hectic and stressful life, this naturally occurring alternate breathing cycle gets disrupted and we suffer from different ailments. These ailments are due to imbalance of autonomic nervous system which can be resolved by practicing alternate nostril breathing, the Nadisodhan pranayama. It’s just like returning back to nature. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7885 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):38-47